Pengembangan Keterampilan Numerasi Dan Kemampuan Kognitif Pada Anak Usia Dini Melalui Media Pembelajaran Menggunakan Bahan Alam (International Forum of Researchers and Lecturers, 2023)
Natural material media is everything learning media that exists in the environment around us to support learning that is very easy and economical but can be used effectively and efficiently which is directly obtained from nature, natural materials that are used as learning media include: stones, branches, seeds, leaves, wood and other natural objects. Natural media becomes something effective and efficient if it is well optimized as material in learning and adjusted to the learning goals that will be achieved by children. One of them is in the development of numeracy and cognitive abilities of children. Natural media can help children develop numeracy skills and cognitive abilities, through various activities that involve critical thinking and problem solving such as counting, comparing, sorting, building, classifying objects and so on.